Evaluation of the inbreeding effect on the milk productivity of Holstein cows - O. V. Rudenko (Аграрная наука Евро-Северо-Востока, 2022)
Inbreeding is an integral part of breeding work today. However, its effect on the economically valuable traits of animals is not identical. The research was carried out in LLC "Вreeding plant «Pushkinskoe» Bolsheboldinsky district of the Nizhny Novgorod region. The data have been obtained from the primary zootechnical records and database «SELEX» – Dairy cattle (n = 950). The animals were divided into 4 groups depending on the degree of inbreeding. Cows with the close degree of inbreeding had the maximum milk yield (9877.9 kg), those with the mild degree had minimal milk yield (9338.11 kg). An increase in the degree of inbreeding had a negative effect on the fat content in milk, which led to its decrease from 3.85 % in the group with outbred animals to 3.64 % in the group with the close degree of inbreeding. There were no significant differences in the protein content in milk between the groups. The lactation stability coefficient decreases as the degree of inbreeding increases. The variability coefficient of milk yield in animals with the close degree of inbreeding is lower than the other groups (10.53 %), the coefficient varies within 5 % according to the fat content in all groups and in terms of protein content in milk within 1.3-2.2 %. Distant and mild inbreeding has a weak positive relationship with milk yield (r = +0.015 and +0.028), close inbreeding leads to its decrease (r = -0.098). Inside the groups, having inbred connections, аn increase in the inbreeding degree leads to a very slight increase in fat content (r = +0.016-0.129) and the lactation stability coefficient (r = +0.063-0.164), the influence of the degree of inbreeding on the protein content in milk is not identical. The relationship between milk yield and fat content in outbred animals is weakly positive (r = +0.26), in cows with mild and distant degree of inbreeding is weakly negative (r = +0.057-0.121), in the group with a close degree it becomes closely negative (r = - 0.677).